Student Achievement - Hackett, Raymond S. (Daily Express, 2007)
This article discusses the findings of a report from the Joseph Rowntree Foundation in the UK on academic achievement of students from low-income backgrounds
Keywords: Academic achievement; Poverty; Socioeconomic background